Die hard [videorecording (DVD)] - McTiernan, John; Willis, Bruce, 1955-; Thorp, Roderick; Rickman, Alan; Thorp, Roderick (Spotlight series (Twentieth Century-Fox Home Entertainment), 2007)
New York detective John McClane has just arrived in Los Angeles to spend Christmas with his family. As he waits for his estranged wife's office Christmas party to break up, German terrorists occupy the building, and McClane wages a one-man war to stop them.